The investigation liffects of selenium on some biochemical parameters in sheep - İbrahim Pirinçci; Ahmet Ateşşahin1 Bülent Elitok2 (Eurasian Journal of Veterinary Sciences)
This study was carried out to investigate the changes in the levels of serum aspartate transaminase (AST), alanine transaminase (ALT), g-glutamyl transpeptidase (g-GT), alkaline phosphatase (ALP), lactic dehydrogenase (LDH), creatine phosfokinase (CPK), total bilirubin (TB), direct bilirubin (DB), total protein (TP), triglyceride, albumin and glucose in sheep experimentally poisoned with selenium. In this study. 18 sheep ai the weight of 50-55 kg were used. Selenium was given intramuscularly at the doses of 0.2 and 0.6 mg/kg. The blood samples were collected at 0.5. 1, 3, 6, 12, 24, 48, 72. 120 and 240!h hours. These samples were analysed for the levels of AST, ALT, GGT. ALP. LDH, CPK, TB, DB. TP, triglyceride, albumin and glucose. In conclusion, selenium caused to increase the levels of AST. ALT, ALP, LDH, CPK, TB, DB and TP in serum of sheep with the experimentally induced selenium poisoning. In contrast, selenium decreased the levels of glucose in serum of sheep.